DAMPAK PERKEMBANGAN EKONOMI DIGITAL DAN AKSES INFORMASI TERHADAP PEMBUKUAN AKUNTANSI - Calosa, Kristiana Greta; Hwihanus (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to analyze the impact of digital economy development and information access on accounting bookkeeping in companies. Using a qualitative approach, data was collected through interviews with five accountants from various companies. The results show that the development of the digital economy has improved the efficiency and accuracy of bookkeeping through automation of the transaction recording process and real-time data access. However, some challenges are also faced, such as data security risks and user training needs. In the long run, automation is expected to continue supporting bookkeeping efficiency and better financial decision-making. Keywords: Digital Economy, Information Access, Bookkeeping Accounting